Analysis of drag, airflow and surface pressure characteristics of a segment rigid sail. Issue 3 (2nd September 2018) - Atkinson, Gregory Mark; Binns, Jonathan
ABSTRACT: Rigid sails have been used on powered ships in the past to reduce fuel consumption and recently there has been renewed interest in this technology. Rigid sails could potentially be used on a wide variety of ships and vessels; therefore, it is necessary to better understand the performance and characteristics of these devices. The present work investigated the airflow and drag characterises of a segment rigid sail using a virtual wind tunnel. Sail surface pressures were also observed and recorded. It was determined that the most effective angle of attack for this type of rigid sail was between approximately 10° and 30°. It was also noted that at larger angles of attack, the presence of a significant wake would limit the effectiveness sails mounted downwind.